Improved load flow formulation for radial distribution networks - Norainon Mohamed; Dahaman Ishak (Institute of Advanced Engineering and Science, 2019)
This paper aims to provide an improved load flow formulation for solving load flow problem in radial distribution networks. The improved algorithm is formulated from the basic Kirchoff’s voltage law. The proposed method does not need any matrix multiplication, and the voltage equation is derived to compute the voltage at each node. The proposed method is then tested on 28-bus, IEEE-33 and IEEE-69 systems of radial distribution networks with different resistance to reactance ratio and different condition of loads. The simulation results from the suggested algorithm show that the proposed method has fast convergence capability compared with other existing methods. A very good agreement is achieved.